Carboxymethylcellulose enhances the production of single-stranded DNA aptamers generated by asymmetric PCR - Redcenko, Oleksij; Draberova, Lubica; Draber, Petr (Analytical biochemistry, 2020)
Nucleic acid aptamers are single-stranded (ss)DNA or RNA oligonucleotides that can take various conformations and bind specifically and with high affinity to selected targets. While the introduction of SELEX (systematic evolution of ligands by exponential enrichment) revolutionized the production of the aptamers, this procedure is impeded by the formation of undesirable by-products reflecting hybridization among complementary oligonucleotides in the ssDNA libraries during asymmetric PCR. To reduce nonspecific amplification we tested cellulose-derived compounds and found that sodium carboxymethylcellulose (CMC) at a concentration 0.05%-0.2% efficiently suppressed production of undesirable large DNA amplicons during asymmetric PCR in the course of SELEX. Formation of the PCR by-products was reduced by CMCs of low and medium viscosity more than by CMCs of high viscosity, and all of them bound to DNA oligonucleotides as determined by electrophoresis in agarose gels. In contrast to CMC, methylcellulose did not reduce the formation of the PCR by-products and did not bind to DNA. DNA aptamers selected in the presence of CMC could be used directly in enzyme-linked immunosorbent-like assay. The combined data suggest that CMC binds weekly to DNA oligonucleotides through hydroxyl groups and in this way inhibits low-affinity DNA-DNA hybridization and enhances the production of specific amplicons in asymmetric PCR.
Keywords: jednovláknová DNA; DNA, Single-Stranded; Polymerase Chain Reaction; Carboxymethylcellulose; methylcelulosa; DNA aptamers; sodná sůl karboxymethylcelulosy; Single-stranded DNA; ELISA; aptamery nukleotidové; aptamerová technika SELEX; PCR; Aptamers, Nucleotide; Carboxymethylcellulose Sodium; Methylcellulose; SELEX Aptamer Technique; polymerázová řetězová reakce; Enzyme-Linked Immunosorbent Assay